Karakteristik Chief Executive Officer (CEO) dan Kualitas Akrual: Bukti Empiris dari Indonesia - Poppy Nurmayanti (Jurnal Akuntansi dan Governance Andalas, 2020)
This study investigates the relationship between CEO characteristics and accruals quality from public firms listed in Indonesia Stock Exchange between 2010 and 2017. This study used two accruals quality measures namely absolute abnormal accruals and performance matched abnormal accruals. Specifically, absolute abnormal accruals are proxied by two proxies, a) the modified Jones model (Dechow et al. 1995) and b) accrual estimation error the augmented specification of Dechow and Dichev model (2002) as suggested by McNichols (2002). Furthermore, performance matched abnormal accruals are proxies by two proxies, a) performance matched abnormal accruals by using Kothari et al. 2005) and b) current accrual. This study identifies CEO characteristics as CEO female, financial work experience, business skill, tenure, and CEO founding. The empirical findings that several CEO characteristics (i.e., CEO female, financial work experience, business skill, tenure, and CEO founding) is significantly associated with accrual quality; these in turn, may affect the quality of the firm’s reporting. Overall, these results are consistent with the prediction of the upper echelons theory and have implication in corporate financial reporting.